Model Based on Machine Learning for the Recognition of images for the Postural Diagnosis of workers in Remote mode (LACCEI, 2024)
This article presents the development of an artificial vision system for the recognition of postures focused on remote modality workers, being a suitable model to work with anyone, regardless of their age, race, sexual orientation or size as the objective of this work is to implement remote work to determine the challenges and possibilities of using this type of work and identify factors to consider before implementation. The work is justified because it is essential to determine if this modality is efficient to carry out the correct measurement of the worker's posture. Having as a result that the angle of 120 ° and 60 ° reveals possible causes of back pain and injuries caused by poor posture or incorrect postural hygiene This means that when the user is sitting in the correct 90° degree posture, it avoids causing serious back injuries in the long term.